Morfology, seed and seedlings quality of Yucca endlichiana and implications in its conservation - Meza-Cota, Ana Bertha; Vargas-Hernández, J. Jesús; Vázquez-Badillo, Mario Ernesto; Villarreal-Quintanilla, José Ángel; López-Aguillón, Ricardo; Florez-López, Celestino (Ecosistemas y Recursos Agropecuarios, 2022)
Yucca endlichiana Trel. is a microendemic species in the state of Coahuila and under special protection status. The objective was to of the study was to know the morphological variability, seed and seedling quality of Y. endlichiana to propose conservation actions. Capsules were collected in more than 30 selected plants in the localities of El Dorado, San Antonio del Jaral and Las Coloradas. To which eight morphological variables were evaluated, seven of seed quality, and one in seedling. The analysis of variance morphologically differentiated the El Dorado seed in the weight of 100 seeds, thickness of the seed and seed coat. In the sanity tests on PDA (potato dextrose agar) and MSA (mannitol salt agar), the localities showed incidence of the fungi Aspergillus niger (61.11% PDA and 66.66% MSA) and A. flavus (50.00% PDA and 50.00% %MSA). There are no significant differences between locations for seed viability, normal and abnormal seedling germination, germination vigor and seedling quality. The optimal values in seed quality and seedlings of Y. endlichiana will facilitate in situ and ex situ conservation in the establishment of forest germplasm production units and seed management in germplasm banks, valuing the selection of individuals in short- and long-term conservation.